(untitled) (Stamford Journal of Microbiology, 2025)
Salmonella is a major food-borne pathogen associated with outbreaks of enteric diseases. Antibiotic-resistant ability of Salmonella is a major concern because of abuse of antibiotics may pose bring risk to humans and animals. This study aimed to isolate and characterize a lytic bacteriophage from a sewage sample with the potential to biologically control instead of chemically control Salmonella in food contamination. Phages are intracellular bacterial viruses; they are obligate and host-specific, and can infect only prokaryotes. Spot test and efficiency of plaque formation (EOP) data indicated that phage Dsi15 had a wide host range and broad lytic ability within the Salmonella spp. Phage Dsi15 confirmed extensive pH (4-11) tolerance, and lengthened thermal (30-50°C) stability. We experienced the effectiveness of phage Dsi15 as a biological control in a food metric when lettuce contaminated with S. Enteritidis ATCC 13076, treated with phage Dsi15 at a multiplicity of infection (MOI) of 1000 at 25°C. The ability of phage Dsi15 to control Salmonella in lettuce was recognized. Treated with phage Dsi15 Salmonella count decreased by 1 log CFU/cm2 at 25°C in lettuce by MOI of 1000. Our findings showed that phage Dsi15 has potential efficiency as a biological control against pathogenic Salmonella in a food matrix. Stam. J. Microbiol. 2025;15(1):1-5